English: English - Haya Fathin Nabila; Mulin Nu'man (Universitas Sarjanawiyata Tamansiswa, 2025)
This study examines the relationship between religious attitudes and students' mathematics learning outcomes at Madrasah Aliyah Negeri. This correlational approach research used a sample of 54 students. Data on religious attitudes were obtained through a questionnaire based on five aspects of religiosity, while mathematics learning outcomes were obtained through midterm summative scores. The Spearman Rank correlation test was used to analyze the data and showed that religious attitude had an insignificant relationship with mathematics learning outcomes. Overall religious attitude has a correlation coefficient of -0,235. Religious attitudes have an important role in shaping students' characters, such as discipline and responsibility, although they are not significantly related to mathematics learning outcomes. This finding provides an important insight that the relationship between religiosity and math learning outcomes is not direct and may be influenced by other factors such as time management or learning motivation. In addition, this study explains the integration of Islamic values in mathematics learning, for example through linking mathematical concepts with verses from the Qur'an. The results of this study contribute to the understanding of how religious values can be integrated into mathematics education, providing a foundation for further research on alternative factors that may mediate the relationship between religiosity and academic achievement.